Information and Communication Technology (ICT) for Online Classes in Economics Education in TU, Nepal (Surkhet Journal, 2023)
This study intends to investigate how ICT is used for online economics classes and how students view online learning. This study has used a mixed-methods research approach to accomplish the objective. The quantitative findings from the student survey and the qualitative data gained from the evaluation of key informant interviews have provided a level of understanding. Total 28 students of Master Level Economics Education admitted in Mahendra Ratna Campus, Tahachal were taken for the study to investigate the issues. TU altered its academic calendar and closed physical sessions beginning on March 24, 2020, following the finding of the first case of COVID-19 in Nepal on January 23, 2020, in an effort to limit the impact on students' learning and time. The university then made the decision to switch to an online teaching mode. The objective of this action research is to analyze the role of ICT for online classes, to measure students’ positive and negative reactions regarding online classes, and the problems underlying in online classes. The major findings of the study include infrastructure need to be enhanced for the expansion of ICT Services and use of ICT in education. The majority of students said that their online learning experience was normal and online classes were of good quality. Infrastructure connectivity is deemed to be adequate. Online learning platform is new among teachers and students and met educational needs and maintained regularity. Smart Phones were major device for remote learning.